Study on Optimal Production Conditions of Fibrinolytic Kinase Derived from the Nereid Worm, Perinereis aibuhitensis Grub - Tuo Song; Jun Cheng; Xiaozhen Diao; Yang Man; Boyu Chen; Haixing Zhang; Jeevithan Elango; Wenhui Wu (Fermentation, 2024)
The fibrinolytic kinase identified in the nereid worm (Perinereis aibuhitensis Grub) displays exceptional kinase activity, stability, and specificity, suggesting its potential as a promising candidate for the advancement of new thrombolytic drugs. In this study, a process was optimized for the production of fibrinolytic kinase using Escherichia coli, and the effects of factors such as inoculum, pH, OD, temperature, inducer concentration, and time on the protein yield were investigated. The optimum points of key parameters were determined by single-factor experiments, and the initial pH, OD, and time were determined to be significant by PB (Plackett–Burman design) with six factors at two levels of experiments. The response surface experiments highlighted the key roles of initial pH and induced OD values, and the convergence of the model and experimental data confirmed the optimal conditions and reasonable fluctuation intervals, which proved the reliability of the model.